Public-Private Partnerships in Land Administration : Analytical and Operational Frameworks - World Bank (World Bank, Washington, DC, 2020)
This report Public-Private Partnerships in Land Administration: Analytical and Operational Frameworks was developed to address knowledge gaps, advance the thinking on how PPPs can be implemented in land administration with appropriate risk mitigation, and explore how the World Bank and other development partners may engage in financing and building capacity in land administration. With its analytical assessments and operational tools, the report intends to support governments (land agencies and government entities tasked with overseeing PPPs) and development partners in better understanding and identifying potential opportunities for PPPs in land administration.